Prevalence of young-onset dementia: nationwide analysis of routinely collected data. Issue 10 (22nd August 2022) - Ryan, Brigid; To, Edith; Ma'u, Etuini; Chan, Amy Hai Yan; Rivera-Rodriguez, Claudia; Curtis, Maurice A; Cullum, Sarah; Cheung, Gary
Abstract : Introduction: Young-onset dementia prevalence is understudied internationally. Previous studies have been limited by low case numbers, reliance on single sources of routinely collected health data for case identification and inclusion of a limited age range. Our objective was to determine the 1-year period prevalence of diagnosed dementia in people aged 0–64 in the entire New Zealand population using routinely collected health data. Methods: A population-based descriptive study was carried out in New Zealand (population 4.8 million) using routinely collected deidentified health data from 2016 to 2020. Dementia cases in seven linked health datasets in the New Zealand Integrated Data Infrastructure were identified using diagnostic codes and/or use of antidementia medication. Prevalence for each of the four study years was calculated by age, sex and ethnicity. Results: From a total population of 4 027 332–4 169 754 individuals aged 0–64, we identified 3396–3474 cases of 'all-cause' dementia in each of the study years (prevalence crude range: 83–84/100 000 people aged 0–64; 139-141/100 000 people aged 30–64 years; 204–207/100 000 people aged 45–64 years). Age-standardised prevalence was higher in males than females. Age-standardised and sex-standardised prevalence was higher in Māori and Pacific People than European and Asian. Discussion: By using a large study population and multiple national health datasets, we have minimised selection bias and estimated the national prevalence of diagnosed young-onset dementia with precision. Young-onset dementia prevalence for the total New Zealand population was similar to reported global prevalence, validating previous estimates. Prevalence differed by ethnicity, which has important implications for service planning.